استثمار الأملاك الوقفية عن طريق الايجار - - أيوب زيدي, - إلهام معروفي; - جمال طرية (Universté ELOUEd-جامعة الوادي, 2022)
يعتبر الوقف من أهم المؤسسات الخيرية والاقتصادية التي عرفتها الإنسانية، باعتبار أحد الصيغ الإنسانية العريقة وهو نظام قديم جدا لكنه كان محصورا في أماكن العبادة ويحظر التصرف في الرقبة وتوجيه المنفعة لجهة معلومة في الحضارات القديمة وقد خصص جزء صغير منه للفقراء والمساكين، وبمجئ الإسلام تطور أصبح الوقف أحد مظاهر الحضارة، حيث عرف نقلة نوعية و ذلك بسبب حث الإسلام على الإنفاق وفعل الخير مصداقا لقوله تعالى ¯لن تنالوا البر حتى تنفقوا مما تحبون وما تنفقوا من شيء فإن الله به عليم ¯.، فقد تعددت أغراض الوقف وتنوعت أهدافه، وانتقل من الصعيد الديني إلى الصعيد الاجتماعي وأصبح له اهتمام خاص ومكانة سامية تليق به حيث وجدوا له منافذ أخرى لتوسيع مجالاته كافة وب ذلك يتوسع الاستغلال الوقفي إلى مجالات أكبر تحقق الاستغلال العام ولكن وبطرق قانونية وفق ما تنص عليه قوانين استغلال الملك الوقفي وبهذا توسع مفهوم الوقف إلى مجال الاستثمار الذي يرمي إلى التنمية الاقتصادية، فأعطوا ب ذلك الوقف وجها اقتصاديا، وأقاموا للمرة الأولى في تاريخ البشرية مؤسسات اقتصادية طويلة الأمد، تقوم على مبدأ خدمة المجتمع، بشكل هو أشبه ما يكون بما يسمى اليوم مؤسسات المجتمع المدني ومن خلال ما سبق ذكره نستطيع القول أن النظام القانوني للوقف العام في التشريع الجزائري لابد للغاية من إيجار الأملاك الوقفية العقارية هو الحصول على موارد مالية تسمح للأوقاف بالنمو والتطور حتى تؤدي عملها المنوط إليها، ولهذا اعتبرنا أن استثمار الأملاك الوقفية عن طريق الإيجار هو عملية تثمن قيمة استغلال الأملاك الوقفية، بل يمكن اعتبارها المنفذ الأصلح على غرار الصيغ الأخرى التي تم استحداثها في استثمار الأملاك الوقفية . ونظرا لهذه الأهمية التي تتميز بها الأملاك الوقفية نجد أن من الناحية التشريعية تدخل المشرع بعدة قوانين ومراسيم تبنت تنظيم وسيرورة الأملاك الوقفية وكيفية التصرف فيها بطرق تتوافق وخاصية المال الوقفي لأن الأصل في الملك الوقفي هو عدم التصرف فيه إلا لأعمال الخير.The endowment is considered one of the most important charitable and economic institutions known to humanity, considering it is one of the ancient human formulas, and it is a very old system, but it was confined to places of worship and it was forbidden to dispose of the neck and direct the benefit to a known destination in ancient civilizations, and a small part of it was allocated to the poor and needy, and with the advent of Islam, the endowment became developed. One of the manifestations of civilization, where he knew a qualitative leap due to Islam's urging to spend and do good, in accordance with the Almighty's saying ¯ You will not attain righteousness until you spend from what you love and whatever you spend, God is All-Knowing of it. To the social level, it has a special interest and a lofty position worthy of it, as they found other outlets for it to expand all its fields. Thus, the endowment exploitation expands to larger areas that achieve general exploitation, but through legal methods, according to the laws of the exploitation of the endowment property, and thus the concept of the endowment expanded to the field of investment that aims To economic development, they gave this endowment an economic face, and for the first time in human history they established long-term economic institutions, based on the principle of community service, in a form that is more like We are what are called today civil society institutions. Through the foregoing, we can say that the legal system of the public endowment in the Algerian legislation is absolutely necessary to rent endowment properties in order to obtain financial resources that allow endowments to grow and develop in order to perform their work entrusted to them, and for this we considered that investing endowment properties through rent is a process that values the value of the endowment. Exploitation of endowment properties, but it can be considered the most suitable outlet, similar to other formulas that have been developed in the investment of endowment properties. In view of this importance of endowment properties, we find that from the legislative point of view, the legislator enters into several laws and decrees that adopted the organization and process of endowment properties and how to dispose of them in ways that correspond to the characteristic of endowment money, because the origin of the endowment property is not to dispose of it except for charitable deeds.
مذكرة ماستر
Keywords: الاستثمار/ الأملاك الوقفية/ الايجار/ المؤسسات الخيرية; Investment / endowment properties / rent / charitable institutions